CRITICAL REALISM IN CHARLES DICKENS’S IN “DAVID COPPERFIELD” - Shockett, Enkelena (Acta Scientiae et Intellectus, 2024)
Using a close reading through the strong analysis of the character development methodology through which the narrative shapes David Copperfield as Victorian novel which opens up interesting perspectives in reading I will highlight the influence of Critical Realism in the work of Charles Dickens. Furthermore, this methodology, which facilitates and accelerates the text comprehension although it is characterized by inter-textuality, will exfoliate remarkably the author’s philosophy and ethics utilized in this work.